The History of the Gulag : from collectivization to the great terror - Khlevniuk, Oleg (Annals communism (Yale University Press), 2004)
"The human cost of the Gulag, the Soviet labor camp system in which millions of people were imprisoned between 1920 and 1956, was staggering. Aleksandr Solzhenitsyn and others after him have written movingly about the Gulag, yet never has there been a thorough historical study of this unique and tragic episode in Soviet history. This book presents the first comprehensive, historically accurate account of the camp system. Russian historian Oleg Khlevniuk has mined the contents of extensive archives, including long-suppressed state and Communist Party documents, to uncover the secrets of the Gulag and how it became a central component of Soviet ideology and social policy."